Groundstate dispersion interaction between pi-conjugated polymers. - Barford, W; Xu, X (2008)
The line-dipole approximation is used to investigate the scaling of the groundstate dispersion interaction, EW, between parallel conjugated polymers of length L and transverse separation D. Both a second-order perturbation theory calculation using the Mott-Wannier exciton model of excited states and a semiclassical analysis of distributed dipoles indicate that at L approximately D there is a crossover from the point-dipole approximation result of EW approximately L2/D6 for L<<d approximately="" d5="" ew="" expected="" for="" l="" of="" result="" the="" thermodynamically="" to="">>D.</d>